Co-Created Messaging for Influenza Vaccination in a High-Risk Hispanic Community Provides Groundwork for COVID-19 Vaccine (Mary Ann Liebert, 2021)
Purpose: Influenza/pneumonia is the eighth leading cause of death in the United States. The 2020?2021 influenza season is predicted to be further impacted by COVID-19 infections. Historical data reflect disproportionate morbidity and mortality rates in the Hispanic population for influenza and COVID-19. Influenza vaccination rates remain low in the Hispanic community. We aim to improve vaccination through a community-led event, partnering with the Cristo Rey School Dallas, located in a zip code with a higher age-adjusted influenza/pneumonia mortality rate. A survey was administered to adults attending the Influenza vaccine event to understand attitudes and perceptions about influenza, vaccination, and effective messaging strategies for the campaign. Methods: Messaging was cocreated with student health ambassadors to promote immunization and delivered through trusted sources. The health department administered vaccines to individuals >age 3 at no cost. Adults were asked to complete a 19-question survey postvaccination offered in both English and Spanish. Results: Two hundred and forty-one of 394 (61.2%) participants completed the survey. Ninety-eight percent identified as Hispanic/Latino, and the majority of surveys were administered in Spanish. Among Spanish language participants, the church bulletins (57.3%) and Spanish language radio (30.5%) were reported to be most effective modes of messaging versus word of mouth (32.9%) and social media (26.3%) for English-speaking participants. Sixteen percent of participants surveyed had never received an influenza vaccine before this event. Conclusion: Cocreated messaging delivered by trusted sources in the Hispanic community led to a successful Influenza vaccine drive with the Dallas County health department.